2019
DOI: 10.1111/1748-8583.12241
|View full text |Cite
|
Sign up to set email alerts
|

Winning at all costs: An exploration of bottom‐line mentality, Machiavellianism, and organisational citizenship behaviour

Abstract: This study seeks to advance the bottom‐line mentality literature by exploring an antecedent and outcome of employee bottom‐line mentality. We build and test a moderated‐mediation model by arguing that the personality trait of Machiavellianism promotes an employee's adoption of a bottom‐line mentality. Moreover, drawing on trait activation theory, we argue that this relationship is fully activated when the employee perceives that the organisation endorses a bottom‐line mentality. To expand our theoretical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 57 publications
2
74
1
1
Order By: Relevance
“…To date, prior research has primarily explored the effects of supervisor BLM in the work domain and mostly from a dysfunctional perspective (e.g. Eissa et al, 2019;Greenbaum et al, 2012;Mawritz et al, 2017;Quade et al, 2020; see colleagues (2019b, 2020) for exceptions). This line of inquiry has shown that supervisor BLM facilitates abusive supervision (Mawritz et al, 2017), lowers employee performance (Quade et al, 2020), increases employee turnover intention (Mesdaghinia et al, 2019), and triggers social undermining behavior (Greenbaum et al, 2012).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…To date, prior research has primarily explored the effects of supervisor BLM in the work domain and mostly from a dysfunctional perspective (e.g. Eissa et al, 2019;Greenbaum et al, 2012;Mawritz et al, 2017;Quade et al, 2020; see colleagues (2019b, 2020) for exceptions). This line of inquiry has shown that supervisor BLM facilitates abusive supervision (Mawritz et al, 2017), lowers employee performance (Quade et al, 2020), increases employee turnover intention (Mesdaghinia et al, 2019), and triggers social undermining behavior (Greenbaum et al, 2012).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…If the employee shares personal work knowledge with colleagues, her/his competitive advantage will be weakened (Eissa et al, 2018). Subordinates with BLMs are likely to win at all costs (Eissa et al, 2019), let alone withhold or conceal knowledge such as how to more effectively get jobs done to avoid losing the competitive advantage. Thus, we hypothesize as follows:…”
Section: Negative Outcomes Of Supervisor Blm Through Subordinate Blmmentioning
confidence: 99%
“…By so doing, our study advances the BLM literature by bringing in a gender lens. Researchers have previously examined various boundary conditions, e.g., employee conscientiousness (Greenbaum et al, 2012), Machiavellianism (Eissa et al, 2019), moral identity (Mesdaghinia et al, 2019), employee core self-evaluations, and employee ambition (Babalola et al, 2020) of BLM and relevant outcomes. However, few BLM studies have explored the moderating role of gender.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In such cases, moral disengagement is more likely to occur. Moreover, Machiavellians, who do not lack moral standards (Schepers, 2003), tend to ignore moral norms or engage in moral disengagement (Dahling et al, 2008;Gabi et al, 2019). Therefore, we suggest that subordinates with high-level Machiavellians are more inclined to respond to an abuser in an unethical way in the face of the lack of reward.…”
Section: Moderating Role Of Machiavellianismmentioning
confidence: 82%